2009
DOI: 10.1007/s10597-009-9246-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Integrative Reminiscence on Depressive Symptomatology and Mastery of Older Adults

Abstract: A quasi-experimental (non-randomized) study was conducted to study the effects of a new intervention The story of your life that combines integrative reminiscence with narrative therapy. The program consists of seven sessions of two hours and one follow-up session after 8 weeks.It is directed at community-dwelling people of 55 years and older with mild to moderate depressive symptoms. After the intervention the participants showed significantly less depressive symptoms and higher mastery, also in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
0
45
0
1
Order By: Relevance
“…The positive effects of integrative reminiscence on depressive symptoms in older adults is well-documented (e.g., Bacher, Kindler, Scheler, & Lerer, 1991; Bohlmeijer, E., Kramer, J., Smit, F., Onrust, S., & Marwijk, H., 2009; Bohlmeijer, E., Smit, F., & Cuijpers, P.; 2003; Fry, 1983; Haight & Dias, 1992; Lamers, Bohlmeijer, Korte, & Westerhof, 2015; Shellman, Mokel, & Hewitt, 2009; Stevens-Ratchford, 1992). In a meta-analysis of the impact of reminiscence and life review on depression in the elderly, Bohlmeijer, Smit, & Cuijpers (2003) found that in 15 randomized controlled trials, reminiscence and life review significantly improved depressive symptoms compared to controls and with large and highly significant effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of integrative reminiscence on depressive symptoms in older adults is well-documented (e.g., Bacher, Kindler, Scheler, & Lerer, 1991; Bohlmeijer, E., Kramer, J., Smit, F., Onrust, S., & Marwijk, H., 2009; Bohlmeijer, E., Smit, F., & Cuijpers, P.; 2003; Fry, 1983; Haight & Dias, 1992; Lamers, Bohlmeijer, Korte, & Westerhof, 2015; Shellman, Mokel, & Hewitt, 2009; Stevens-Ratchford, 1992). In a meta-analysis of the impact of reminiscence and life review on depression in the elderly, Bohlmeijer, Smit, & Cuijpers (2003) found that in 15 randomized controlled trials, reminiscence and life review significantly improved depressive symptoms compared to controls and with large and highly significant effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The finding indicated that subject's perceptions of treatment efficacy, or therapist competency did not influence the outcome measures [28]. However, Bohlmeijer et al (2009) proposed people who had more positive and general attitude towards reminiscence therapy would benefit more than people who were less interested in that [37]. We will examine these factors in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides alleviating the depression symptoms, reminiscence therapy was proved to improve self-esteem [34], life satisfaction [35], psychological well-being [36], personal mastery [37,38] and loneliness [39,40]. However, the conclusion is not consistent [41-43].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of simple reminiscence evidence is limited with regard to its effects on mental health . Several research findings point to the positive effects of reminiscence in reducing depressive symptoms (Bohlmeijer, Valenkamp, Westerhof, Smit, & Cuijpers, 2005;Chiang et al, 2010;Kwon, Cho, & Lee, 2013;Pinquart & Forstmeier, 2012;Shellman, Mokel, & Hewitt, 2009;Stinson, Young, Kirk, & Walker, 2010), improving cognition (Cotelli, Manenti, & Zanetti, 2012;Kwon et al, 2013;Pinquart & Forstmeier, 2012;Woods, Spector, & Jones, 2005), mood (Cotelli et al, 2012;Lin, Dai, & Hwang, 2003;Woods et al, 2005), quality of life (Kwon et al, 2013), satisfaction with life (Chiang, Lu, Chu, Chang, & Chou, 2008;Lin et al, 2003), self-esteem (Chao et al, 2006;Chiang et al, 2008), well-being (Chiang et al, 2010;Pinquart & Forstmeier, 2012;Reis-Bergan, Gibbons, Gerrard, & Ybema, 2000), mastery (Bohlmeijer et al, 2005;Bohlmeijer, Kramer, Smit, Onrust, & Van Marwijk, 2009;Pinquart & Forstmeier, 2012), ego integrity, purpose in life, preparation for death, mental health and social integration (Pinquart & Forstmeier, 2012). Nevertheless, despite the potential beneficial of reminiscence therapy, authors are unanimous in recognizing constraints, particularly in methodological designs, that hampers an effective assessment of the impact of this therapy (Cotelli et al, 2012;Lin et al, 2003;Lopes, Afonso, & Ribeiro, 2014;Pinquart & Forstmeier, 2012;Westerhof et al, 2010;Woods et al, 2005).…”
Section: Introductionmentioning
confidence: 99%